The Development of The Library of Social Studies Programe, Faculty of Education, Sisaket Rajabhat University - สารรัตน์ ธันยพงศ์ (Research and Development Journal Sisaket Rajabhat University, 2020)
This purposes of this research were to : 1) study the library states and service problems of The library in Social Studies Programe, Faculty of Education, Sisaket Rajabhat University; 2) study the guidance for the library development 3. develop the library under the Good Media, Good Environment and Good Service;: 3) Gs, and 4) compare the clients’ behavior for using the library before and after the development, and clients’ satisfaction assessment. The sample of the research consisted of 172 schools administrator, teachers, staffs and Bachelor Degrees students, Academic year of 2010. The sample used Purposive Sampling. The data were collected by a pre and post clients statistics record, a structured interview form, and the clients’ satisfaction and suggestion from. The data were analyzed by study the library state and service problems, study the clients’ need, study the 3 Gs from the clients’ statistics, group discussion, structured interview for arranging the library development and began development followed the 3 Gs , reading promotion activities, reading promotion activities participants’ satisfaction assessment, and study the clients’ suggestions toward the library services after the developed 3 Gs library and presented withdelineation. The research statistics used mean, percentage, and standard deviation. The results found that: The study result for the library’s state, problems and the guidance for development found that there were many students used the library as the library statisticsrecords, their satisfaction was moderated. The group discussion between the researcher, researcher assistants, librarians, and library committees agreement said that the library should be developed as the efficiency, modem, and standard library by using the 3 Gss. The reading promotion activities, and the reading behavior promotion activities should be arranged for the students at the efficiency, modern, and standard 3 Gs library, all subject areas text books, modern multimedia should be supplied, and enough for learning and teaching, the library’ atmosphere should be the lively library such as a modern decoration, comfortable, and convenience services for motivation the students to use the library, the librarian should be provided for friendly guiding, advice and assist the clients for retrieve. The overall for all activities was at good level (= 4.49). When it considered in individual aspect, found that there were 4 activities were at very good level, ranged from the highest to the lowest mean score: Activity 7; Happy reading in a happy day, ( = 4.70), Activity 4; Dictionary and encyclopedia retrieve contest ( = 4.60), Activity 5 Library Fan Club ( - 4.60), and Activity 6; Reading Champion ( = 4.60). There were 4activities were as good level, ranged from the highest to the lowest mean score: Activity 2;Caravan Library( = 4.50), Activity 8; Reading Poet Contest ( = 4.50), Activity 1,Library guidance activity ( = 4.30), and Activity 3; Telling story from a book ( = 4.10), Activity 1, The overall aspect for clients’ satisfaction toward the library services after development as the 3 Gs was at high level ( = 3.46). When it consider in individual aspect found that, there were 3 aspects were at high level, ranged from the highest to the lowestmean score: the librarian and activities aspect ( = 3.48), location and atmosphere aspect ( = 3.45), and text book and learning multimedia aspect (= 3.44)